Veterinarians' attitudes to chronic pain in dogs. (1st November 2014) - Bell, A.; Helm, J.; Reid, J.
Abstract : Veterinary surgeons in the UK were invited to complete an internet survey concerning their attitudes to chronic pain in dogs. UK veterinary surgeons numbering 215 completed surveys in full along with 48 worldwide specialists in anaesthesia and 37 worldwide specialists in oncology. Osteoarthritis, dental and aural disease, vertebral and spinal cord conditions, neoplasia and skin conditions were considered important causes of chronic pain in dogs. UK practitioners used significantly fewer classes of analgesic drugs regularly than either category of specialist. The major barriers to adequate treatment of chronic pain were reported as difficulties with pain assessment, expense of drugs, and difficulties with owner compliance. Illustrations of six common neoplastic conditions were used and scored for pain according to prior experience by practitioners. All six conditions were consistently described as involving some degree of pain with primary bone tumour and oral tumour, causing severe pain and moderate to severe pain, respectively. Years since graduation and specialist status affected the pain scores attributed to the conditions. There was a significant correlation between the pain score attributed to the illustrated condition, and the tendency to administer analgesia.